The concept of nefesh in the Old Testament - Neto, Willibaldo Ruppental (Vox Scripturae - Revista Teológica Internacional, 2016)
This article aims to build a propose of conceptualization of the word nefesh in the Old Testament, indicating that it is a word that, besides meaning breath, throat, desire and life, it can also be understood as a “soul”, if this mean the human being itself, in its situation of necessity, related to his body, his life, and even the risk of death.